J Agric Sci Bot 2018
DOI: 10.35841/2591-7897.2.1.25-36
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of carp pituitary extract and Ovaprim during captive breeding of Cat Fish, Pabda (Ompok pabda).

Abstract: Ompok pabda, popularly known as "Butter cat fish", is a freshwater species native to India, Bangladesh, Pakistan, and Myanmar. This species is an indigenous catfish belongs to the family Siluridae of the order Siluriformes. It is listed as endangered fish species [1][2][3][4]. The fish has a wide geographical distribution covering Afghanistan, Bangladesh, Myanmar, the Indus plain and adjoining hill area of Pakistan, the North East States of India particularly in Bihar and West Bengal during the early 1970s. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
1
0
1
Order By: Relevance
“…Meanwhile, other factors include water current, light, pH, temperature, and the degree of rainfall. The pituitary extract gave a higher percentage of fertilization in this study, this was not in agreement with the report of (Chattopadhyay, 2018) who reported a low fertilization rate in C. gariepinus induced with pituitary extract.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Meanwhile, other factors include water current, light, pH, temperature, and the degree of rainfall. The pituitary extract gave a higher percentage of fertilization in this study, this was not in agreement with the report of (Chattopadhyay, 2018) who reported a low fertilization rate in C. gariepinus induced with pituitary extract.…”
Section: Discussioncontrasting
confidence: 88%
“…This agreed with (Hossain et al 2012) who worked on C. gariepinus fish induced with synthetic and natural hormone. The broodstock induced with pituitary gland had higher survival (82.31%) after six weeks compared to the broodstock induced with ovaprim (79.68%), this agreed with (Chattopadhyay, 2018) The growth of the larvae monitored for six weeks revealed a significant difference (P<0.05) among the treatments at the early stage, meanwhile, there was no significant difference in the SGR and RGR, this agreed with (Abdul et al, 2017) who recorded a similar growth rate after the feeding trial for 28 days, the same trend was reported by Ndimele and Owodeinde (2012). However, Ikechukwu et al (2019) explained that the growth among the fishes treated with ovaprim and pituitary gland extract was not significantly different.…”
Section: Discussionsupporting
confidence: 82%